Efektivitas Metode Problemâ€Based Learning dalam Pembelajaran Mata Kuliah Teori Psikologi Kepribadian II - Supratiknya, -; Kristiyani, Titik (Faculty of Psychology, Universitas Gadjah Mada, 2005)
This study aims at uncovering: (1) whetherÂ the problemâ€based learning (PBL) method is effective to teach a theoretical subject such as Personality Psychology II; (2) how effective is theÂ PBL method compared to the traditional methodÂ to teach a theoretical subject such as Personality Psychology II; and (3) whether the teacherfactors affect the effectiveness of the PBL methodÂ to teach a theroretical subject such as Personality Psychology II. Three available classes ofÂ Subjects enrolling in Personality PsychologyII, two of which were taught with the PBLÂ method by a seniorâ€maleâ€demanding teacher andÂ a juniorâ€femaleâ€easyâ€going teacher respectivelyÂ while the other one was taught with the traditional method by the seniorâ€maleâ€demandingÂ teacher, participated in the study. Designed as aÂ quasiâ€experimental research, the results showedÂ that the first two aims of the study were confirmed. Regarding the teacher factors effect, theÂ study showed a direct and positive relation between the Subjectsâ€™ number of study hour andtheir achievement disregarding both the teaching method and the teacher factors as well as aÂ complicated relation between the Subjectsâ€™ learning satisfaction and their achievement presumâ€ably involving both the teaching method andÂ the teacher factors with the various aspects ofÂ teacher competencies. A further study on the lastÂ matter seems to be needed.